Factors associated with failure of passive transfer of immunity and morbidity in spring-born beef and dairy calves during the first 30 days of life - Male Here, Rischi Robinson; McGee, Mark; McAloon, Catherine; Byrne, Andrew W.; Earley, Bernadette (Frontiers in Veterinary Science, 2026)
The failure of passive transfer of immunity (FPT) in calves is associated with increased susceptibility to infectious diseases, leading to higher morbidity rates and reduced herd productivity. The present study evaluated dam and calf characteristics, and herd-level and calf-level management practices associated with passive immune measures, FPT, and morbidity during the first 30 days of life in Irish (suckler) beef and dairy calves. Datasets were collected from herd-level [66 beef farms (391 calves), 77 dairy farms (674 calves)], and calf-level [9 beef farms (377 calves), 8 dairy farms (916 calves)] studies conducted in spring 2015 and 2016, respectively. Passive immunity was assessed in calf serum collected 1–14 days post-birth using ELISA (total IgG; ELISA-IgG), clinical analyzer (total protein; TP-CA), and BRIX refractometer (total solids; TS-BRIX). Calf FPT status was defined using current-cut-offs specific to Irish calves and literature-cut-offs. The current-cut-offs of ELISA-IgG were ≤9 and ≤12 mg/mL for beef and dairy calves, respectively, whereas TP-CA ≤60 g/L and TS-BRIX ≤8.4% were used for both calf types. The literature-cut-offs for both calf types were ELISA-IgG <10 mg/mL, TP-CA <52 g/L, and TS-BRIX <8.4%. Calf morbidity data were recorded by farmers. The datasets were analyzed using mixed-effects linear and logistic regressions, and Cox proportional hazard models. Risk factors associated with passive immune measures (continuous outcome) and/or FPT in beef calves included dam diarrhea vaccination, dam parity, timing of birth in calving season, breed, perinatal problems, and timing and method of colostrum feeding, and in dairy calves included dry period length, dam parity, calf sex, breed, calving supervision, and type of colostrum feeding. Passive immune measures were not associated with morbidity in beef or dairy calves; however, depending on test and cut-offs, FPT was associated with increased morbidity hazard in beef but not in dairy calves. Risk factors for morbidity in beef calves included cow-calf housing location and dam parity, and in dairy calves included cow-calf separation, pen cleaning, dam parity, breed, calving assistance, and colostrum feeding method. The present study underscores the importance of selecting appropriate passive immune tests and cut-offs for FPT and highlights modifiable management practices to improve calf health.